The Son of Man’s Judgment of Nations. A Framework for Diaconal Spirituality? - Gärtner, Stefan (Diaconia, 2025)
This article examines Matthew 25:31-45 as a theological framework for diaconal spirituality. It argues that this pericope conveys both an ethical imperative and the promise of Christ’s presence. Moving beyond an imitation of Christ (imitatio Christi), it highlights the encounter with Christ (visitatio Christi) in vulnerable people. The article considers reciprocity in care, challenges the caregiver-care recipient dichotomy, and underscores the equal significance of diaconia alongside liturgy and the proclamation of the gospel. Rooted in eschatological hope, the argument affirms that pro-social action is constitutive to the church’s mission and serves as an action-based proclamation of the gospel.